Presentation is loading. Please wait.

Presentation is loading. Please wait.

H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = - 392.5 kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = +102.5 kJ H 2 O(g)

Similar presentations


Presentation on theme: "H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = - 392.5 kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = +102.5 kJ H 2 O(g)"— Presentation transcript:

1 H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g)  H 2 O(l) ΔH = kJ

2 H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g)  H 2 O(l) ΔH = kJ kJ

3 H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g)  H 2 O(l) ΔH = kJ kJ kJ

4 H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = kJ H 2 O(g)  H 2 O(l) ΔH = kJ kJ kJ kJ

5 4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ

6 4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ 4 PCl 5 (g) → 4 PCl 3 (g) + 4 Cl 2 (g) ΔH = kJ Flip, x 4

7 4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ 4 PCl 5 (g) → 4 PCl 3 (g) + 4 Cl 2 (g) ΔH = kJ 4 PCl 3 (g) → P 4 (s) + 6 Cl 2 (g) ΔH = kJ Flip

8 4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) P 4 (s) + 6 Cl 2 (g) → 4 PCl 3 (g) ΔH = kJ PCl 3 (g) + Cl 2 (g) → PCl 5 (g) ΔH = kJ 4 PCl 5 (g) → 4 PCl 3 (g) + 4 Cl 2 (g) ΔH = kJ 4 PCl 3 (g) → P 4 (s) + 6 Cl 2 (g) ΔH = kJ 4 PCl 5 (g) → P 4 (s) + 10 Cl 2 (g) ΔH = kJ

9 N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ

10 N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ Flip

11 N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ N 2 (g) + 2 O 2 (g) → 2 NO 2 (g) ΔH = -33 kJ Flip

12 N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ N 2 (g) + 2 O 2 (g) → 2 NO 2 (g) ΔH = -33 kJ 4 H 2 O(l) → 4 H 2 (g) + 2 O 2 (g) ΔH = kJ x 2

13 N 2 (g) + 3 H 2 (g) → 2 NH 3 (g) 2 NH 3 (g) + 4 H 2 O(l) → 2 NO 2 (g) + 7 H 2 (g) ΔH = -57 kJ 2 NO 2 (g) → N 2 (g) + 2 O 2 (g) ΔH = +33 kJ 2 H 2 O(l) → 2 H 2 (g) + O 2 (g) ΔH = kJ 3 2 NO 2 (g) + 7 H 2 (g) → 2 NH 3 (g) + 4 H 2 O(l) ΔH = +57 kJ N 2 (g) + 2 O 2 (g) → 2 NO 2 (g) ΔH = -33 kJ 4 H 2 O(l) → 4 H 2 (g) + 2 O 2 (g) ΔH = kJ N 2 (g) + 3 H 2 (g) → 2 NH 3 (g)ΔH = kJ

14 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ

15 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ Flip, x 3

16 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ 6 FeO(s) + 2 CO 2 (g) → 2 Fe 3 O 4 (s) + 2 CO(g) ΔH = kJ x 2

17 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ 6 FeO(s) + 2 CO 2 (g) → 2 Fe 3 O 4 (s) + 2 CO(g) ΔH = kJ 6 Fe(s) + 6 CO 2 (g) → 6 FeO(s) + 6 CO(g) ΔH = -3.6 kJ Flip, x 6

18 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g) 2 Fe(s) + 3 CO 2 (g) → Fe 2 O 3 (s) + 3 CO(g) ΔH = kJ 3 FeO(s) + CO 2 (g) → Fe 3 O 4 (s) + CO(g) ΔH = kJ FeO(s) + CO(g) → Fe(s) + CO 2 (g) ΔH = +0.6 kJ 3 Fe 2 O 3 (s) + 9 CO(g) → 6 Fe(s) + 9 CO 2 (g) ΔH = kJ 6 FeO(s) + 2 CO 2 (g) → 2 Fe 3 O 4 (s) + 2 CO(g) ΔH = kJ 6 Fe(s) + 6 CO 2 (g) → 6 FeO(s) + 6 CO(g) ΔH = -3.6 kJ 3 Fe 2 O 3 (s) + CO(g) → 2 Fe 3 O 4 (s) + CO 2 (g)ΔH = kJ

19 C 2 H 4 (g) + 6 F 2 (g)  2 CF 4 (g) + 4 HF(g) H 2 (g) + F 2 (g)  2HF(g)  H = – 537 kJ C(s) + 2 F 2 (g)  CF 4 (g)  H = – 680 kJ 2 C(s) + 2 H 2 (g)  C 2 H 4 (g)  H = kJ

20 C 2 H 4 (g) + 6 F 2 (g)  2 CF 4 (g) + 4 HF(g) H 2 (g) + F 2 (g)  2HF(g)  H = kJ C(s) + 2 F 2 (g)  CF 4 (g)  H = kJ 2 C(s) + 2 H 2 (g)  C 2 H 4 (g)  H = kJ 2 H 2 (g) + 2 F2(g)  4 HF(g)  H = kJ 2 C(s) + 4 F 2 (g)  2 CF 4 (g)  H = kJ C 2 H 4 (g)  2 C(s) + 2 H 2 (g)  H = kJ C 2 H 4 (g) + 6 F 2 (g)  2 CF 4 (g) + 4 HF(g)  H = kJ

21 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g)

22 ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ

23 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ

24 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ

25 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g) ΔH° f = kJ

26 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ Flip, x 3

27 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ Flip

28 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l)ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l)ΔH° f = kJ ½ N 2 + ½ O 2 (g) → NO(g)ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ x 2

29 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g)ΔH = (ΔH° f ) = kJ

30 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ ½ N 2 (g)+ ½ O 2 (g) → NO(g)ΔH = (ΔH° f ) = kJ 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g)ΔH = kJ

31 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g) ½ N 2 (g) + O 2 (g) → NO 2 (g) ΔH° f = kJ H 2 (g) + ½ O 2 (g) → H 2 0(l) ΔH° f = kJ ½ H 2 (g) + ½ N 2 (g) + 3/2 O 2 (g) → HNO 3 (l) ΔH° f = kJ ½ N 2 (g) + ½ O 2 (g) → NO(g) ΔH° f = kJ 3 NO 2 (g) → 3/2 N 2 (g) + 3O 2 (g) ΔH = -3(ΔH° f ) = kJ H 2 0(l) → H 2 (g) + ½ O 2 (g) ΔH = -(ΔH° f ) = kJ H 2 (g) + N 2 (g) + 3 O 2 (g) → 2 HNO 3 (l)ΔH = 2(ΔH° f ) = kJ ½ N 2 (g)+ ½ O 2 (g) → NO(g)ΔH = (ΔH° f ) = kJ 3 NO 2 (g) + H 2 O(l) → 2 HNO 3 (l) + NO(g)ΔH = kJ ΔH = [2(ΔH° f ) + ΔH° f ] – [3(ΔH° f ) + ΔH° f ]


Download ppt "H 2 S(g) + 2 O 2 (g)  SO 3 (g) + H 2 O(l) H 2 S(g) + 2 O 2 (g)  H 2 SO 4 (l) ΔH = - 392.5 kJ H 2 SO 4 (l)  SO 3 (g) + H 2 O(g) ΔH = +102.5 kJ H 2 O(g)"

Similar presentations


Ads by Google